Correlation of medial longitudinal arch morphology with body characteristics and locomotive function in community-dwelling older women: A cross-sectional study. (10th June 2021) - Nakao, Hidetoshi; Imaoka, Masakazu; Hida, Mitsumasa; Imai, Ryota; Tazaki, Fumie; Morifuji, Takeshi; Hashimoto, Masashi; Nakamura, Misa
Purpose: This cross-sectional study aimed to investigate the effects of foot arch deformities on physical characteristics, muscular strength, and motor function in older women depending on the presence or absence of pain. Methods: Overall, 145 community-dwelling women aged 65 to 90 years were included in this study. We measured the foot arch height ratio (AHR, dorsal height/truncated foot length) and classified participants with AHR values above, below, or within 1.5 standard deviations into the high-arched group (HAG), Low-Arched Group (LAG), or normal-arched group (NAG), respectively. We also compared body characteristics (age, height, weight, body mass index (BMI), and skeletal mass index), muscle strength (handgrip strength and intrinsic foot strength (IFS)), and locomotive function (two-step value and gait speed) among the three groups. Results: Locomotive examination and muscle strength showed significant differences among the three groups only in the presence of pain; in the two-step test, HAG, NAG, and LAG values were 0.98 cm/cm, 1.19 cm/cm, and 1.18 cm/cm, respectively. The IFS measured 19.2 N, 24.2 N, 31.0 N, respectively, in the HAG, NAG, and LAG. Conclusion: This study suggests that decreased IFS affects the mobility function of high-arched feet in older women. Although there was no significant difference in the evaluation of pain, HAG showed the highest average value, which is considered to contribute to the decreased two-step value. It has been suggested that a high-arched foot in the presence of pain is associated with IFS weakness and may affect the decline of mobility function in older women.